Digital Competence and Culture Influencing Digital Transformation Effectiveness among Millennials (POLITEKNIK LP3I JAKARTA, 2026)
Digital transformation has become a strategic priority for higher education institutions to improve service quality, operational efficiency, and organizational performance. The success of digital transformation depends not only on technological infrastructure but also on employees' digital competence and organizational digital culture. This study aims to examine the influence of digital competence and digital culture on digital transformation effectiveness among millennial employees of Universitas Terbuka Regional Offices in Sumatra. A quantitative research approach was employed using a cross-sectional survey design. Data were collected from 343 millennial employees through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that digital competence has a positive effect on digital transformation effectiveness (β = 0.412), while digital culture also positively influences digital transformation effectiveness (β = 0.368). The structural model demonstrates satisfactory explanatory power with an R² value of 0.625, indicating that both independent variables explain 62.5% of the variance in digital transformation effectiveness. These findings suggest that employees' digital capabilities and a supportive organizational digital culture are essential drivers of successful digital transformation in higher education institutions. The study contributes to the digital transformation literature by providing empirical evidence from Indonesia's distance higher education context and offers practical implications for strengthening employee competencies and fostering a sustainable digital culture to improve organizational performance.